KONTRIBUSI HASIL HUTAN BUKAN KAYU TERHADAP PENDAPATAN MASYARAKAT SEKITAR HUTAN LARANGAN ADAT GHIMBO POTAI KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Sutami Sutami; Muhammad Mardhiansyah; Defri Yoza (JURNAL ILMU-ILMU KEHUTANAN, 2021)
Ghimbo Potai Banned Indigenous Forest is a prohibited forest that has a variety of wood species and non-timber forest products used by communities around the forest, along with the times, the use of non-timber forest products began to decline. The purpose of this study was to determine the types of non-timber forest products that are used by the community in Ghimbo Potai Banned Indigenous Forest  and to determine the contribution of non-timber forest products to the community income around Ghimbo Potai Banned Indigenous Forest . This research was conducted with a qualitative descriptive method. The number of respondents was 170 respondents from Koto Tibun Village and Pulau Tinggi Village. The result show that Ghimbo Potai Banned Indigenous Forest  still has non-timber forest products that can still be used such as chempedak (Artocarpus integer), petai (Parkia speciosa), long jack (Eurycomma longifolia), rattan (Calamus rotang), rambutan (Nephellium sp.), langsat (Lansium domesticum Corr), tampoi (Beccauera sp.), tempunik (Artocarpus rigidus), durian (Durio zibethinus), jelutong (Dyera costulata), terap (Artocarpus sp.), pulasan (Nephelium mutabile), dogfruit (Archidendron pauciflorum) and the eyebrowed thrush (Turdus obscurus). The contribution of non-timber forest products in Koto Tibun Village was Rp. 596,400,000.00 per year, so the percentage of non-timber forest product revenue to total income was 19.56% and Pulau Tinggi Village no longer takes or utilizes existing non-timber forest products in Ghimbo Potai Banned Indigenous Forest .